Implementation of a high fidelity simulation based training program for physicians of children requiring long term invasive home ventilation: a study by ISPAT team - Bas Ikizoglu, Nilay; Atag, Emine; Ergenekon, Pinar; Gokdemir, Yasemin; Uyan, Zeynep Seda; Girit, Saniye; Kilinc Sakalli, Ayse Ayzit; Erdem Eralp, Ela; Cakir, Erkan; Guven, Feray; Aksoy, Mehmet Emin; Karadag, Bulent; et al. (Frontiers in Pediatrics, 2024)
Introduction: The number of children requiring long-term invasive home ventilation (LTIHV) has increased worldwide in recent decades. The training of physicians caring for these children is crucial since they are at high risk for complications and adverse events. This study aimed to assess the efficacy of a comprehensive high-fidelity simulation-based training program for physicians caring for children on LTIHV. Methods: A multimodal training program for tracheostomy and ventilator management was prepared by ISPAT (IStanbul PAediatric Tracheostomy) team. Participants were subjected to theoretical and practical pre-tests which evaluated their knowledge levels and skills for care, follow-up, and treatment of children on LTIHV. Following the theoretical education and hands-on training session with a simulation model, theoretical and practical post-tests were performed. Results: Forty-three physicians from 7 tertiary pediatric clinics in Istanbul were enrolled in the training program. Seventy percent of them had never received standardized training programs about patients on home ventilation previously. The total number of correct answers from the participants significantly improved after the theoretical training (p<0.001). The number of participants who performed the steps correctly also significantly increased following the hands-on training session (p<0.001). All of the 43 participants who responded rated the course overall as good or excellent. Conclusion: The knowledge and skills of clinicians caring for children on LTIHV can be enhanced through a comprehensive training program consisting of theoretical training combined with hands-on training in a simulation laboratory.